Establishment of a UPLC-MS/MS Method for Studying the Effect of Salt-Processing on Tissue Distribution of Twelve Major Bioactive Components of Qing'e Pills in Rats. (17th September 2020) - Hou, Jingxia; Lin, Shangyang; Lu, Jinlan; Wu, Yu; Wu, Li; Chen, Zhipeng; Li, Weidong
Abstract : Qing'e pills is clinically used for treating osteoporosis in postmenopausal women in China. Eucommiae Cortex and Psoraleae Fructus are the main herbs of Qing'e pills and are both required to be salt-processed. In order to study the influence of salt-processing on the tissue distribution of Qing'e pills, a UPLC-MS/MS method was established for studying the tissue distribution of 12 main bioactive ingredients of Qing'e pills in rats. The linear relationships of the 12 compounds in each tissue were good. The method was fully validated for its selectivity, accuracy, precision, stability, matrix effect, and extraction recovery. Then, the validated method was successfully applied for simultaneous determination of the 12 chemical components in Qing'e pills in tissues for the first time. Areas under the curve (AUC) results showed that, except for pinoresinol diglucoside, psoralen, and isopsoralen, the distribution of the other components was increased in the kidney, uterus, ovary, and testes. Relative targeting efficiency (RTE) results showed that all 12 chemical components targeted the kidney and sexual organs. The results indicated that the Eucommiae Cortex and Psoraleae Fructus after salt-processing could significantly increase the distribution of components to the kidney and generative organs.